Studi Mikromorfologi Kapsul dan Spora serta Implikasinya terhadap Pengelompokkan Lumut Pogonatum P. Beauv. (Polytrichaceae) - - Windahayati; Ardinis Arbain; - Syamsuardi (Universitas Andalas, 2014)
The micromorphology capsule and spore are important characters for identification and clarification of problematic taxa in Bryophyta. The number of Pogonatum species in West Sumatra are still unclarified. The purpose of this study is to identify and to make a Pogonatum cluster based on micromorphology of capsule and spore characters. This study has been conducted from March to August 2013. Samples were directly collected in two exploration routes namely Cagar Alam Lembah Anai (Kandang Ampek - Mega Mendung route) and Singgalang Mountain (Pandai Sikek - Top Singgalang route). The micromorphology of capsule and spore of Pogonatum were observed using a Scanning Electron Microscope (SEM). The results showed that five species of Pogonatum (P. ciratum, P. microstomum, P. macrophyllum, P. Teysmannianum , and P. cf. urnigerum) were identified. The key characters of Pogonatum was nematodontous peristome teeth, monolete spore type, prolate spore shape with granulate and echinate ornamentation. Cluster analysis of 44 individuals indicated that Pogonatum tends to be in the same group. Based on micromorphological analysis, the results supported that Pogonatum was similar to Polytrichum. Keywords: peristome teeth, Pogonatum, Polytrichum, SEM, spore